The urgency of regulating forfeiture of assets gained from corruption in Indonesia - Hufron, Hufron; Fikri, Sultoni (Faculty of Law, University of Muhammadiyah Malang, 2024)
Corruption threatens democratic principles that highly value transparency, accountability, and integrity. Indonesia must continuously innovate in its efforts to combat corruption. Establishing more comprehensive asset forfeiture regulations is crucial, given the increasing rates of corruption. This study addresses two main research questions: 1) Asset forfeiture regulations in various countries; 2) The urgency of regulating asset forfeiture for corruption crimes in Indonesia. This research employs a normative legal research method, using a literature study to collect legal materials. The findings indicate that various countries have established and implemented asset forfeiture regulations with different concepts, namely Conviction-Based Asset Forfeiture and Non-Conviction-Based Asset Forfeiture. However, Indonesia does not yet have specific provisions and only treats asset forfeiture as an additional penalty.